332. Spinal Infections: Clinical and Microbiological Characteristics in our Urban Referral Health Center. (31st December 2020) - Ogbebor, Osakpolor; Abdulmassih, Rasha; Como, James D; Bhanot, Nitin
Abstract: Background: There has been an increasing trend in spinal infections (SI) in the U.S. over recent years. We sought to characterize the clinical and microbiological characteristics of SI at our hospital. Methods: We conducted a retrospective review of SI over a 3-year period (2016 - 2019) utilizing ICD codes for data retrieval. Search terms included vertebral osteomyelitis, discitis, and epidural abscess. SPSS was used to compute the data. Results: Of the initially screened 254 patients, 166 were included for analysis. Pertinent demographics were: mean age 59 years, male (61.4%), obese (44.5%), diabetic (25%), and drug-users (20%). Lumbosacral involvement was most common (69.8%); epidural abscess was present in 51.8% of patients. 15.7% had existing hardware. Overall, 79.5% (132/166) of cases had a positive culture from at least one site: blood 56.6% (94/166), CT-guided 83.5% (56/67), and surgical 51.1% (24/47). Of those patients with negative blood cultures, 22% (16/72) had pathogen recovery by CT-guided methods and 33% (24/72) from surgical specimens. S aureus was the most common pathogen isolated at 53.7% (71/132): MSSA comprised 38.6% (51/132) and MRSA 15.2% (20/132). The mean CRP (8.46 vs 15.83 mg/dL; P< 0.001), and WBC (9.08 vs 13.18 k/mcL; P< 0.001) were higher in culture-positive as compared to culture-negative cases. Mean ESR and temperature more than 100.4 o F did not differ significantly between these two groups. The 8-week median recurrence rate was 11.4%, of which nearly half had index S aureus bacteremia. Frequency of organisms isolated Association of mean inflammatory markers with positive cultures Conclusion: Our study affirmed that S aureus is the most common cause of SI, of which MSSA was predominant. Epidural abscess was encountered in a substantial fraction of our case population. Leukocytosis and elevated CRP tended to predict culture-positive infection, whereas ESR and fever did not. As recommended in the IDSA Vertebral Osteomyelitis guidelines, blood cultures were obtained in all cases, which yielded positive results in more than half of patients. Pathogen recovery was further improved to nearly 80% with supplemental deep tissue sampling, thus highlighting the opportunity to enhance microbiological diagnosis at our institution. Disclosures: All Authors : No reported disclosures